2017
DOI: 10.1177/1352458517695468
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of teriflunomide in patients who received prior disease-modifying treatments: Subgroup analyses of the teriflunomide phase 3 TEMSO and TOWER studies

Abstract: Abstract:Teriflunomide is a once-daily oral immunomodulator approved for relapsing-remitting multiple sclerosis (MS). The objective of this post hoc analysis of the phase 3, pooled TEMSO (NCT00134563) and TOWER (NCT00751881) dataset is to evaluate the effect of teriflunomide treatment on annualised relapse rate and disability worsening across patient subgroups defined according to prior diseasemodifying therapy exposure. This analysis provides further supportive evidence for a consistent effect of teriflunomid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…A study comparing relapse activity between patients who remained on injectable DMTs and patients who switched due to tolerability issues to teriflunomide or DMF, found that switchers had a lower risk of relapse (HR 0.43, p=0.048) or any disease activity (HR 0.55, p=0.035) compared with patients who remained on injectable therapy (Saraceno et al, 2019). In a post-hoc analysis of the pooled phase 3 TEMSO and TOWER studies, teriflunomide 14 mg was associated with reductions in ARR and risk of disability worsening across all subgroups defined by prior DMT exposure in the previous 2 years (≥2 prior DMTs, 1 prior DMT, or no prior DMT) compared with placebo (Freedman et al, 2018b). In the real-world Teri-PRO study, patients who switched to teriflunomide from an injectable DMT had statistically significant increases in treatment satisfaction across all four TSQM domains (effectiveness, side effects, convenience, and global satisfaction) after 48 weeks (Coyle et al, 2018).…”
Section: Efficacy and Treatment Satisfaction In Patients Switching Fr...mentioning
confidence: 99%
“…A study comparing relapse activity between patients who remained on injectable DMTs and patients who switched due to tolerability issues to teriflunomide or DMF, found that switchers had a lower risk of relapse (HR 0.43, p=0.048) or any disease activity (HR 0.55, p=0.035) compared with patients who remained on injectable therapy (Saraceno et al, 2019). In a post-hoc analysis of the pooled phase 3 TEMSO and TOWER studies, teriflunomide 14 mg was associated with reductions in ARR and risk of disability worsening across all subgroups defined by prior DMT exposure in the previous 2 years (≥2 prior DMTs, 1 prior DMT, or no prior DMT) compared with placebo (Freedman et al, 2018b). In the real-world Teri-PRO study, patients who switched to teriflunomide from an injectable DMT had statistically significant increases in treatment satisfaction across all four TSQM domains (effectiveness, side effects, convenience, and global satisfaction) after 48 weeks (Coyle et al, 2018).…”
Section: Efficacy and Treatment Satisfaction In Patients Switching Fr...mentioning
confidence: 99%
“…And also, in the here presented in vivo paradigm long-term (constant) teri unomide application did not negatively affect remyelination indicating that prolonged application as occurring in the context of the RMS therapy will not interfere with neuroregeneration. It is therefore tempting to speculate that the here described restoration of myelinated axons could in fact also contribute to the reduced disability progression in treated patients (TEMSO, ClinicalTrials.gov number NCT00134563; TOWER, ClinicalTrials.gov number NCT00751881) (43).…”
Section: Discussionmentioning
confidence: 98%
“…Different from previous real-world studies, all the patients included in this study were not on any DMT at least for 1 year prior to teriflunomide initiation. Since the efficacy of teriflunomide was reported in subgroup analyses of pivotal studies to be different between patients with and without prior DMT [ 22 ], the data of our study might better represent the effectiveness and safety data of teriflunomide in treatment-naïve patients.…”
Section: Discussionmentioning
confidence: 99%